2003
DOI: 10.1556/aphyt.38.2003.1-2.15
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics Features of Willow-feeding Aphids

Abstract: Willow-feeding aphid colonies were sampled on scattered trees (Salix alba) from April until November, in 1999. The collected individuals belonged to 9 aphid species of 3 families (Lachnidae, Chaitophoridae, Aphididae). The aphid populations showed two peaks in May and in October. The indirect negative effect of the rainfall seems to be responsible for this temporal pattern. The Shannon diversity also exhibited spring and autumn peaks during the year. The willow-feeding aphid guild seasonally rearranged, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…A previous study by Kaakeh and Dutcher found a significant reduction in aphid numbers collected post-rainfall compared to pre-rainfall [ 34 ]. This is in accordance with other studies in different systems [ 35 , 36 ]. This may account for the lack of a significant difference in the upper canopy in 2020 compared to 2019 as the rainfall was greater in 2020 (3 mm) compared to 2019 (0.06 mm).…”
Section: Discussionsupporting
confidence: 94%
“…A previous study by Kaakeh and Dutcher found a significant reduction in aphid numbers collected post-rainfall compared to pre-rainfall [ 34 ]. This is in accordance with other studies in different systems [ 35 , 36 ]. This may account for the lack of a significant difference in the upper canopy in 2020 compared to 2019 as the rainfall was greater in 2020 (3 mm) compared to 2019 (0.06 mm).…”
Section: Discussionsupporting
confidence: 94%
“…We assume this was due to the low population densities of aphids at the beginning of the observation period. We have no data on aphid dynamics in this area but substantial increases in the abundance of tree-dwelling aphids from April to May are recorded for temperate regions, for instance, by Sequeira & Dixon (1997), Jarošík & Dixon (1999), Molnár (2003) and Durak (2008). However, we have no explanation for the high gaster mass and low concentration of sugars in workers returning to nest trees in April compared to the other groups of workers (Figs 3, 5, 7).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies suggested that population dynamics of the GWA is highly variable between years, with insects observed on willows for up to 20 weeks. 17,19 For instance, in other temperate parts of the world, GWA populations peak in mid-autumn, 31 and remain visible even through winter months. 19,32 Their presence in willows during winter seems to depend, among other factors, on willow cultivar, as adults were observed overwintering in Salix lasiandra Benth.…”
Section: Discussionmentioning
confidence: 99%